Habitat Potensial Satwa Mangsa Harimau Sumatera (Panthera tigris sumatrae) di Terangun - Beutong Kawasan Ekosistem Leuser - Fazlurrahman, Ridha; Dharma, Wira; Wobisono, Hariyo T. (Bioscientist : Jurnal Ilmiah Biologi, 2024)
PThe Sumatran tiger is an apex predator that has an important role as a controller of ecosystem balance. Tigers are highly adaptive wildlife, so they can be found in various habitat types, ranging from tropical forests, swamps, mangroves, to grasslands in the Himalayan foothills. This study aims to determine the habitat conditions of Sumatran tiger prey animals in Terangun - Beutong as an alternative to one of the Sumatran tiger release locations. Data collection was carried out for 1 year in July 2022-2023. The data used in this study are data on the presence of tigers and prey animals at the research location. The equipment used for Sumatran tiger data collection are maps of the study area, Global Positioning System/GPS, manual compass, karmantel rope, data tabulation sheet/tallysheet, stationery, surveillance cameras, digital cameras for documentation, mattresses, sleeping bags, hammocks, tents, cooking utensils, field clothes, raincoats, and carrier bags. Data analysis was conducted using ArcGIS 10.3 software, by selecting spatial analysis work. The research results of this research modeling show that the Terangun - Beutong area is one of the areas that has potential habitat for Sumatran tigers.